Exercise-mediated improvement of depression in patients with gastro-esophageal junction cancer is linked to kynurenine metabolism. (4th May 2019) - Herrstedt, Anita; Bay, Marie L.; Simonsen, Casper; Sundberg, Anna; Egeland, Charlotte; Thorsen-Streit, Sarah; Djurhuus, Sissal S.; Magne Ueland, Per; Midttun, Øivind; Pedersen, Bente K.; Bo Svendsen, Lars; de Heer, Pieter; et al.
Abstract: Background: Exercise may improve depression in cancer patients, yet the molecular mechanism behind this protection is poorly understood. Here, we aimed to explore the link between exercise and regulation of kynurenine (Kyn) metabolism and inflammation in patients with operable gastro-esophageal junction (GEJ) cancer patients, who improved significantly in depression score with exercise training. Material and Methods: Fifty GEJ cancer patients were allocated to 12 weeks of supervised training twice weekly including interval-based aerobic exercise and resistance training, or standard care. Depression score was evaluated by HADS, and blood samples and muscle biopsies were collected for determination of Kyn metabolism and inflammation across the intervention. Results: Depression scores decreased by −1.3 points in the exercise group ( p < 0.01), whereas no changes were observed in the control group. Plasma 3-hydroxykynurenine (HK), a Kyn metabolite giving rise to other neurotoxic metabolites, increased by 48% ( p <0.001) in the control group, while exercise training attenuated this accumulation. The production of HK is induced by inflammation, and while we observed no differences in systemic pro-inflammatory cytokines, exercise training ameliorated the treatment-induced intramuscular inflammation. Moreover, exercise has been suggested to convert Kyn to the neuroprotective metabolite, kynurenic acid (KA), but despite marked functional and muscular exercise-mediated adaptations, we did not observe any enhancement of KA production and related enzyme expression in the muscles of GEJ cancer patients. Conclusion: Exercise training reduced symptoms of depression in patients with GEJ cancer, and this effect was associated with an exercise-dependent attenuation of the inflammation-induced conversion of Kyn to neurotoxic metabolites.